Fatores de risco para pneumonia associada a ventilação mecânica: estudo de caso controle - MARSOLA, Lourival Rodrigues (Universidade Federal do Pará, 2013)
Ventilator-associated pneumonia (VAP) is the most common nosocomial infection in intensive care unit (ICU) patients. Understanding the risk factors for VAP can help to assess prognosis and devise and test preventive strategies. To identify the factors associated with development of VAP and its incidence, a restrospective non-matched case-control study was conducted in a 10-bed surgical-medical intensive care unit at a university hospital in Belém city, Brazil, from January 2003 to July 2004. The primary outcome measured was risk factors associated with VAP, which was defined according to The Centers for Diseases Control and Prevention. Demographic and time-dependent variables reflecting ventilation, nutrition, drug exposure, associated morbidities and invasive devices were analyzed. Twenty seven VAP patients and 27 controls were studied. Crude rate of pneumonia and incidence of VAP were, respectively, 10.6% and 12.3 episodes/1000 VM-days. The mean time for the onset of VAP was 14.29 ± 9.16 days. Mean ICU length of stay in patients with and without VAP were 34.2 ± 27.7 and 15.4 ± 13.6 days, respectively (p=0.003). Crude mortality was similar in both groups, 66.7% for cases and 55.6% for controls (OR=1.60; 95% confidence interval [CI] 0.53- 4.82; p=0.576). Univariate analysis demonstrated aerosol therapy (OR=4.75; p=0.01) and neuromuscular blockade (OR=8.61; p=0.003) associated with higher risk of VAP. In summary, neuromuscular blockade and aerosol therapy were associated with an increased risk for the development of ventilator-associated pneumonia and both are potentially modifiable risk factors.